Answer:
Maximum attained at point
![\left((11)/(3),(11)/(3),(11)/(3)\right).](https://img.qammunity.org/2020/formulas/mathematics/college/u25i2jkt1a306i64hod9x00lfzd49we21h.png)
Minimum attained at point
![(0,0,0)](https://img.qammunity.org/2020/formulas/mathematics/college/kea6mqtp4acczuelo9pjx0cav45dbzgkmu.png)
Explanation:
Write f(x,y,z) as
![f(x,y,z)=(xyz)/(2(xyz)^(1/2))=(√(xyz))/(2),](https://img.qammunity.org/2020/formulas/mathematics/college/kgj3eozr3c49lthb21atcaff1xhmg1rkgr.png)
and let
![g(x)=x+y+z-11.](https://img.qammunity.org/2020/formulas/mathematics/college/fw3n622h9enihb804dqncc1l1vewf2bf7t.png)
We have to optimize the function f(x,y,z) subject to g(x,y,z)=0. Using Lagrange multipliers, we have to solve the system of equations below:
![\\abla f(x,y,z)=\lambda \\abla g(x,y,z),](https://img.qammunity.org/2020/formulas/mathematics/college/j4gsbedg99bw91thc1iek47loqzlf1bxa9.png)
![g(x,y,z)=0.](https://img.qammunity.org/2020/formulas/mathematics/college/7vabnm1ykg34k0ls7cipjqteq9t63u806h.png)
Or equivalently:
![f_x=\lambda g_x,](https://img.qammunity.org/2020/formulas/mathematics/college/m6f2syt7ej9cgd40xfs0d92sdpfou0h2ef.png)
![f_y=\lambda g_y,](https://img.qammunity.org/2020/formulas/mathematics/college/axg2lyrhbvk3ffauu52u3stm14c8v9xczi.png)
![f_z=\lambda g_z,](https://img.qammunity.org/2020/formulas/mathematics/college/x9cjl66i2ytgc9u0ib2kpy70dwg3xphza5.png)
![x+y+z=11.](https://img.qammunity.org/2020/formulas/mathematics/college/hc21mel6e68g3on540e12u84spfzznklen.png)
Now we calculate the partial derivatives of f and g:
![f_x=(yz)/(4√(xyz)),\ \ f_y=(xz)/(4√(xyz)),\ \ f_x=(xy)/(4√(xyz)).](https://img.qammunity.org/2020/formulas/mathematics/college/6me0lkonb33ea4cq44a3qfxor0up1wegvn.png)
![g_x=g_y=g_z=1.](https://img.qammunity.org/2020/formulas/mathematics/college/vav1nbf9lfhftkusflbfarkanhuqrhsx67.png)
Then we have to solve the system of equations
![\begin{cases}\hfil (yz)/(4√(xyz))=\lambda & (1) \\ \hfil (xz)/(4√(xyz))=\lambda & (2) \\ \hfil (xy)/(4√(xyz)) =\lambda & (3) \\ x+y+z=1 & (4) \end{cases}](https://img.qammunity.org/2020/formulas/mathematics/college/x8ttmrjs8tj8hpnp2ivywg79e8qaghy8ur.png)
From equation (1) and (2) we get by cancelling the common factor
that x = y.
Similarly, using (2) and (3) we get that y = z. Therefore, we have that x = y = z, and by equation (4), we obtain that
![x+y+z=3x=11 \Longrightarrow x=(11)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/9bgry5h91mf3nyj4pvkzi766bxp47tloi8.png)
Since the function f(x,y,z) is non-negative, then
is a point where f attains an absolute maximum, and
![f\left((11)/(3),(11)/(3),(11)/(3)\right)=(11√(33))/(8)\approx 3.51](https://img.qammunity.org/2020/formulas/mathematics/college/hs9b4x399vfoqfblm8km7mg5sunqw1m4id.png)
Because of the non-negativity of the function, we see that at
f attains an absolute minimum, and its value is
![f(0,0,0)=0.](https://img.qammunity.org/2020/formulas/mathematics/college/ey0nmmceu93z8x5gzinrvsq3n708nssruu.png)